2020
DOI: 10.1002/rcm.8652
|View full text |Cite
|
Sign up to set email alerts
|

MSPolyCalc: A web‐based App for polymer mass spectrometry data interpretation. The case study of a pharmaceutical excipient

Abstract: Rationale In contrast to biological polymers, synthetic macromolecules consist of distributions of sizes, chemical compositions, functionalities and eventually architectures. The mass spectrum of a synthetic polymer may exhibit a tremendous number of signals. The availability of suitable IT tools to support interpretation is key. Methods A web‐based tool is presented: MSPolyCalc. It offers a set of functionalities, including the calculation of polymer distributions, molecular formulae and a match evaluation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…It was observed that the molar mass difference between two consecutive peaks of the same kind, was 408.10 Da, which corresponds to the mass of a thiol‐ene monomer unit (see Figure 4 ). The assignment was made using MSpolycalc software, [ 40 ] considering the thiol‐ene as repetitive unit and different end‐groups at both chain ends. The end‐groups considered were C 12 H 18 O 4 , C 6 H 14 S 2 O 2 , C 4 H 6 N, and C 14 H 21 O 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the molar mass difference between two consecutive peaks of the same kind, was 408.10 Da, which corresponds to the mass of a thiol‐ene monomer unit (see Figure 4 ). The assignment was made using MSpolycalc software, [ 40 ] considering the thiol‐ene as repetitive unit and different end‐groups at both chain ends. The end‐groups considered were C 12 H 18 O 4 , C 6 H 14 S 2 O 2 , C 4 H 6 N, and C 14 H 21 O 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The spray voltage was set to 3.2 kV. The calculations were carried out based on the PolyCalc web-based assignment tool [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is accessible from the ms.epfl.ch web page, which should be opened preferably through the Google Chrome browser. Similar to Apm 2 S, the Aom 2 S application is written in pure JavaScript using the library available on https://github.com/cheminfo/molecular-formula (the whole project and code access can be found at https://github.com/cheminfo/nucleotide-website), whereas the data visualization is based on the software https://github.com/npellet/visualizer 16,17 . Importantly, all the calculations applied during data treatment are performed locally in the browser, with no data transferred to the server.…”
Section: Methodsmentioning
confidence: 99%
“…This software is directly accessible through a web browser without any need for installation. It is integrated into the ms.epfl.ch toolbox together with an Apm 2 S tool previously reported for MS/MS data interpretation for peptides/small proteins 14,15 and polymers 16 . Fine‐tuning of various parameters and the versatility and speed of the Aom 2 S functionalities are demonstrated in selected examples of modified DNA and RNA molecules.…”
Section: Introductionmentioning
confidence: 99%